The Environmental Responsibility of the World’s Largest Banks - Ryszawska Bożena (Economics and Business, 2018)
Sustainability transition is changing the role and function of banks, specially their products and services also in relation to stakeholders. Banks are one of the main actors supporting the transition to sustainable economy. The purpose of this study is to emphasise the role of world’s largest banks in that process. Banks are slowly responding to the new demand of sustainability and responsibility, and they try to align with it. The paper is based on an overview of the world’s five largest banks that employ corporate social responsibility (CSR) reporting standards, together with detailed enumeration of pro-environmental activities included in the reports. The first section of this paper presents the most popular approaches to the problem at hand, as reported in professional literature. Section two presents the characteristics of the CSR actions in banks. The third section discusses the environmental actions of the biggest banks in Global Reporting Initiative (GRI) reporting the most popular standard for reporting non-financial information. And the last part of the paper presents the conclusions resulting from the article. The research was conducted using a variety of sources, such as scientific articles, statistical data, CSR reports of the world’s largest banks, as well reporting principles and standard disclosures. The basic method used in the process of writing was a critical analysis of literature and reports concerning the CSR reporting standards, environmental responsibilities of different kinds of entities, as well as own observations based on special reports of banks. In the article, also the analysis of financial market data, induction method and comparison method have been used. The main conclusions of the analysis of the CSR reports disclosed by the world’s largest banks confirm all three of the theses presented in the article. The findings suggest that the banks under study can be regarded as environmentally responsible entities. Their reports and disclosures are produced according to the internationally recognized standards. There are also critical opinions about the standards for reporting environmental information, but the weaknesses of reporting these aspects do not undermine the benefits of using the GRI guidelines.